Identification of viral genes involved in pepper mottle virus replication and symptom development in Nicotiana benthamiana - Fang, Miao; Yu, Jisuk; Kwak, Hae-Ryun; Kim, Kook-Hyung (Frontiers in Plant Science, 2022)
Pepper mottle virus (PepMoV) infects primarily Capsicum species, including pepper and bell pepper which are important vegetable and spice crops in Korea. We have previously collected 13 PepMoV isolates from nine regions comprising five provinces, causing different symptoms on inoculated indicator host plants in Korea. To further identify the responsible symptom determinant(s) and explore viral protein functions of PepMoV, two out of 13 isolates, including 134 and 205136, were used in this study. Isolate 134 causes necrosis and yellowing, while 205136 causes severe mottle and yellowing symptoms on Nicotiana benthamiana. All chimeric and site-directed mutants contain the PepMoV 134 genome as a backbone with specific regions switched for those from counterparts of PepMoV 205136. Effects of all mutants compared with 134 after inoculation onto N. benthamiana by agroinfiltration. Results from our study provide direct evidence that the helper component-proteinase (HC-Pro) and the nuclear inclusion protein b (NIb)-coat protein (CP) regions are involved in virus accumulation and symptom determinants. In addition, we mapped to amino acid residues tyrosine, glycine, and leucine at position 360, 385, and 527, respectively, in the HC-Pro region participate in faster viral accumulation or movement in the plant. The residue valine at position 2773 of NIb plays an essential role in isolate 134 symptom development. As part of this study, we seek to gain insight into viral factors involved in the PepMoV infection cycle and a better understanding of plant-virus interactions. These findings complement the insufficiency of the gene function study of the PepMoV virus and provide a novel perspective for the protein function study of the Potyvirus.